Personality factors involved in suicidal behaviour - Philip, Alistair E. (The University of Edinburgh, 1968)
The aim of the study, to provide information cm the personality characteristics of persons who have attempted suicide, was prompted by the leak of psychological information on persona attempting suicide and by the presence of a considerable body of psychiatric and social information on suicidal behaviour In Edinburgh. It was felt that a descriptive psychological study would complement the psychiatric and social work studies of Kessel (1963) and McCulloch (1965).